Justin Martyr Invents Judaism - Boyarin, Daniel (Church history, 2001)
The historiography of Judaism in the rabbinic period (together with its implications for the history of Christianity) had been, until quite recently, founded on the assumption that the kind of historical information that rabbinic legends could yield was somehow directly related to the narrative contents that they displayed, which were understood as more or less reliable depending on the critical sensibility of the scholar. This scholarship was not, of course, generally naïve or pious in its aims or methods. A recurring question within such research had to do with the question of the credibility of a given text or passage of rabbinic literature or the recovery of its “historical kernel.” For the method or approach that I take up, all texts are by definition equally credible, for the object of research is the motives of the construction of the narrative itself, that is taken to attest to the political context of its telling or retellingrather than to the context of the narrative's content. All texts inscribe the social practices within which they originate, and many also seek to locate the genealogy of those social practices in a narrative of origins, producing a reversal of cause and effect. This reversal is a mode of narration that is particularly germane to the project of replacing traditional patterns of belief and behavior (“We have always done it this way”) with new ones that wish nevertheless to claim the authority, necessarily, of hoary antiquity—in short, to the invention of orthodoxies.